Clinical and radiological criteria for the differential diagnosis between asbestosis and idiopathic pulmonary fibrosis: Application in two cases - Stufano, Angela; Scardapane, Arnaldo; Foschino Barbaro, Maria Pia; Soleo, Leonardo; Corradi, Massimo; Lovreglio, Piero (La Medicina del Lavoro, 2021)
Introduction: Idiopathic pulmonary fibrosis (IPF) and asbestosis are pulmonary interstitial diseases that may present overlapping clinical aspects in the full-blown phase of the disease. For both clinical entities the gold standard for diagnosis is histological examination, but its execution poses ethical problems, especially when performed for preventive or forensic purposes. Objective: To evaluate the application of internationally accepted clinical, anamnestic and radiological criteria for differential diagnosis between asbestosis and IPF, and to assess the ability to discriminate between the two diseases. Even if clinically similar, the two diseases present extremely different prognostic and therapeutic perspectives. Methods: Two clinical cases of IPF are reported, in which the differential diagnosis was made by studying occupational exposure to asbestos, the onset and progression of clinical symptoms, and the identification of specific radiological elements by means of chest High Resolution Computed Tomography (HRCT). Results: The diagnosis of IPF could be made on the basis of the absence of significant exposure to asbestos, the early onset and rapid progression of dyspnea and restrictive ventilatory defects, in association with a pulmonary radiological pattern characterized by peculiar elements such as honeycombing. Discussion: The diagnostic procedure adopted to make a differential diagnosis with asbestosis provides practical clinical elements facilitating the differentiation between the two forms of pulmonary fibrosis, a fundamental aspect of the activity of the occupational physician.